Agents' Preferences, the Equity Premium, and the Consumption-Saving Trade-Off : An Application to French Data - Pommeret, Aude (IMF Working Papers; Working Paper, 2001)
This paper aims to measure the risk premium on French equities during 1960-92 and to evaluate how well theoretical models based on various representations of agents' preferences can explain it. Aside from the standard, time-additive utility function with constant relative risk aversion, three other utility functions are reviewed: a recursive utility function, a habit formation utility function, and a utility function that accounts for the interdependence of preferences. Both calibration and econometric estimations show that none of the studied marginal changes in the representation of agents' preferences are sufficient to solve both the equity premium puzzle and the risk-free rate puzzle.